2017
DOI: 10.5539/ijps.v9n3p35
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Caring-Uncaring Emotional (CUE) Inventory as a Measure of Affective, Callous-Unemotional Psychopathy Traits in a Community Sample of Adults

Abstract: Affective-interpersonal features such as callousness, meanness, or interpersonal antagonism, are regarded as essential to psychopathy. It has been proposed that assessment of the affective dimension of psychopathy may be relevant for risk assessment purposes and for intervention and treatment purposes. It may be constructive to have available brief measures of the affective dimension of psychopathy in both youth and adult populations. The current study represents a second validation study of a new, brief, self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 46 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…The CUE Inventory was designed to measure affective traits of psychopathy. In two studies of community samples of adults (Semel, 2016(Semel, , 2017, the CUE was found to have high internal consistency reliability (α = .91 and .93, respectively). The CUE was found to have high correlations with an expanded, 36-item version of the Levenson Self-Report Psychopathy Scale (LSRP; Levenson, Kiehl, & Fitzpatrick, 1995) that was developed by Christian and Sellbom (2016), and with multiple subscale measures of callous affect from several established adult and youth psychopathy measures.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CUE Inventory was designed to measure affective traits of psychopathy. In two studies of community samples of adults (Semel, 2016(Semel, , 2017, the CUE was found to have high internal consistency reliability (α = .91 and .93, respectively). The CUE was found to have high correlations with an expanded, 36-item version of the Levenson Self-Report Psychopathy Scale (LSRP; Levenson, Kiehl, & Fitzpatrick, 1995) that was developed by Christian and Sellbom (2016), and with multiple subscale measures of callous affect from several established adult and youth psychopathy measures.…”
Section: Methodsmentioning
confidence: 99%
“…Five of the 11 items included in the APM Meanness scale were selected from the Caring-Uncaring Emotional (CUE) Inventory (Semel, 2016(Semel, , 2017. The CUE Inventory was designed to measure affective traits of psychopathy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation